PERAN KONSELING APOTEKER TERHADAP PENGETAHUAN PENGGUNAAN OBAT DENGAN SEDIAAN KHUSUS DI KETANGGUNGAN – BREBES - Muhammad Dwi Suprobo; Nia Fadillah (Jurnal Ilmu Farmasi dan Farmasi Klinik, 2020)
ABSTRACT Counseling is a precious job as known as pharmacists have a provide pharmaceutical services. Counseling given to the publics for drug therapy, treatment, and the drugs with special dosage form is very important to increase publics knowledge. The purpose of this study was to increase the awareness of pharmacists to counseling provide to the public, and increase the public knowledge when using the drugs with special dosage form in Ketanggungan – Brebes regency. Fifty respondents who participated in this study with observasional cohort design. The data collection in pre-test and post-test prospective. Analysis test used is non parametric t test using Wilcoxon alternative test. The last education status of respondents was dominated by Senior High School and the monthly visit to the pharmacy was less than five times as 27 respondents. The results obtained from this study are p = 0.001 and the mean difference is 11.22 with pre-test score mean was 27,54 and post-test was 38,76. There are significant results on the knowledge of the use of drugs with special dosage form after the pharmacist provides counseling. Keywords: pharmacist, counsleing, drugs, pharmaceutical care, knowledge